2020
DOI: 10.1186/s40008-020-0177-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Advantage Following (CAF) development strategy, Aid for Trade flows and structural change in production

Abstract: The terms "structure" and "structural change" (also referred to as "structural transformation") have yet been used with different meanings and interpretations in the economic literature, but they usually refer to long-term and persistent shifts in the sectoral composition of economic systems (Syrquin 2010). Since the first economic development theoreticians such as Paul Rosenstein-Rodan, Arthur Lewis and Albert Hirschman, structural change, broadly defined as the reallocation of resources away from agriculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 60 publications
(47 reference statements)
0
12
0
2
Order By: Relevance
“…In addition, a number of authors emphasize that structural adjustment requires a transition of the economy to a qualitatively different level of industrial development based on the introduction of the concept of smart specialization (Benner, 2019;Kroll, 2019;D'Adda, Guzzini, Iacobucci and Palloni, 2019;Sotarauta, 2018). Gnangnon, (2020) in his work conducted a comparative analysis of structural changes in production in 81 countries. The results showed that the best results are in the countries that have adopted the CAF development strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, a number of authors emphasize that structural adjustment requires a transition of the economy to a qualitatively different level of industrial development based on the introduction of the concept of smart specialization (Benner, 2019;Kroll, 2019;D'Adda, Guzzini, Iacobucci and Palloni, 2019;Sotarauta, 2018). Gnangnon, (2020) in his work conducted a comparative analysis of structural changes in production in 81 countries. The results showed that the best results are in the countries that have adopted the CAF development strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gnangnon (2020c) looked at how AfT connects with the development strategy of the countries on the basis of comparative advantage following (CAF) in influencing the level of structural reform in production activities. The study was carried out using an unbalanced panel data set, which involved 81 recipient countries from the year 1996 to 2016.…”
Section: Aid For Trade Effectivenessmentioning
confidence: 99%
“…The relationship between development strategy (CAD/CAF) proxied by TCI and economic outcomes has attracted widespread attention in the past decades and there have been a large number of studies in this area which articulated theoretical and empirical ways in it contributes to economic outcomes. Empirical studies investigate macroeconomic outcomes, such as growth of GDP per capita (Lin, 2003;Bruno et al, 2015), poverty reduction (Lin and Liu, 2006;Siddique, 2016), structural change in production (Gnangnon, 2020). However, evidence on the exact impact of CAF/CAD has been mixed.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…However, another line of growing literature leaded by the New Structural Economics (NSE), argues that institutional variables themselves are endogenously shaped by a country's development strategy. Subsequent studies (Gnangnon, 2020;Lectard and Rougier, 2018;Siddique, 2016;Bruno et al, 2015;Lin and Liu, 2006;Lin, 2003) did nd evidence of the impact of comparative advantage (CAF/CAD) development strategy on macroeconomic outcomes.…”
Section: Introductionmentioning
confidence: 99%